Pengendalian Kualitas Produk Furniture pada Toko Hilya Furniture Kota Serang - Asep Munir Hidayat; Lina Maulida (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Quality control is an important part of the production process to ensure that the products produced meet the set standards. This study aims to test the application of product quality control on furniture at the Hilya Furniture Store in Serang City. The research method used is a qualitative descriptive approach, with data collected through observation, interviews, and documentation during the Practical Work Lecture (KKP) activities. The results of the study show that the quality control process at the Hilya Furniture Store is still carried out simply, starting from checking raw materials, production processes, to checking the final product before being marketed. The main problems include the limitations of the quality recording system and the lack of systematic quality control standards. In addition, the lack of the use of technology in the quality monitoring process is an obstacle in maintaining product consistency. Therefore, it is necessary to implement a more structured quality control system, including the preparation of standard operating procedures (SOPs), regular quality recording, and training for the workforce to improve product quality and customer satisfaction on an ongoing basis.